Asymmetric Wave Distributions of Tropical Cyclones Based on CFOSAT Observations. Issue 4 (9th April 2021) - Shi, Yanping; Du, Yan; Chu, Xiaoqing; Tang, Shilin; Shi, Ping; Jiang, Xingwei
Abstract: Observations of the China‐France oceanography satellite are used to investigate the wave distribution's asymmetry during tropical cyclone (TC) from August 2019 to August 2020. The spatial distribution of TC waves is analyzed based on an individual case, six ocean basins, and TCs categories. A study of super typhoon Hagibis shows that the highest significant wave height (SWH) appears on the typhoon track's right side. Further analysis reveals that the highest SWH is located on the right (left) side of TC tracks in the Northern Hemisphere (Southern Hemisphere). In the Western North Pacific, North Atlantic, Eastern North Pacific, and North Indian Ocean, the highest SWH is on the right side of TCs of 251, 260, 130, and 118 km, respectively. In the South Pacific and South Indian Ocean, the highest SWH is on the left side of 70 and 128 km. According to the TC categories, the largest (smallest) departure happens during the weakest (strongest) TC. The intensifying of TC favors the wavefield's growth and reduces the asymmetry of the wave height's distribution. Both the asymmetric wind fields and the land's orographic effects impact the TC wave's distribution. In the Eastern North Pacific, the TC wind is the weakest, but the departure is not the smallest, probably due to the left continent bounding the wave energy's propagation. Plain Language Summary: Wind waves are an essential factor in coastal marine economy industries by changing sea level and impacting coastal projects, maritime navigation, and other marine affairs. During tropical cyclones (TCs), there are often intense winds that induce disastrous wind waves. Understanding wave height distribution under TC wind forcing is critical to preventing TC disasters. Under asymmetric wind forcing, the significant wave heights (SWHs) has an asymmetric distribution during TC. Based on the China‐France oceanography satellite observations, this study found that the highest SWH is located on the right (left) side of TC tracks in the Northern (Southern) Hemisphere. However, the skewness of the wave distribution depends on the TC category and ocean basin width, both of them determining the TC strength and wind structure. In addition, the nearby continent has an additional effect on the wave distribution. Key Points: China‐France oceanography satellite observed significant asymmetry in the spatial distributions of wave heights during tropical cyclones (TCs) The highest significant wave height is located on the right (left) side of TCs in the Northern (Southern) Hemisphere Asymmetry of wind fields plays an important role in wave distribution, as does the influence from nearby continents